HRM Practices and Intellectual Capital Architecture: Fostering Ambidexterity in MNCs - Lakshman, C.; Dupouët, Olivier; Bouzdine-Chameeva, Tatiana (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
Organizational ambidexterity has been well researched. Yet, the human resource perspective on this is non-existent. We contribute by providing an empirical understanding of HRM practices at a large MNC encompassing both structural and contextual ambidexterity. Our revelatory case design provides an in-depth investigation of a French MNC. Findings suggest that an intellectual capital configuration, with relatively high levels of human, social, and organizational capital respectively is essential for fostering ambidexterity. Additionally, both a human-capital enhancing HR system and an administrative HR system aids ambidexterity. We discuss the intellectual capital architecture, HR practices, theoretical contributions, limitations, and directions for further research.